2007
DOI: 10.1158/1535-7163.mct-06-0613
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antitumor properties of a novel cyclin-dependent kinase inhibitor, P276-00

Abstract: Cyclin-dependent kinases (Cdk) and their associated pathways represent some of the most attractive targets for the development of anticancer therapeutics. Based on antitumor activity in animal models, a variety of Cdk inhibitors are undergoing clinical evaluation either as a single agent or in combination with other approved drugs. In our anticancer drug discovery program, a novel series of flavones have been synthesized for evaluation against the activity of Cdk4-D1. This enzyme catalyzes the phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 51 publications
(29 reference statements)
3
81
0
1
Order By: Relevance
“…6) is a highly speciWc inhibitor of CDK2 (IC 50 = 10 nM), which is much less selective toward CDK1 (IC 50 = 110 nM) and CDK4 (IC 50 = 130 nM), with no signiWcant activity toward 12 other kinases tested (IC 50 = 2 M). It showed potent antiproliferative eVects against various human cancer cell lines, such as MCF-7 and H-460 (Joshi et al 2007). Several phase I/II clinical studies with P279-00 have been initiated, such as an open-label, multicenter phase I/II study of selective cyclin-dependent kinase inhibitor P276-00 in combination with radiation in subjects with recurrent and/or locally advanced squamous cell carcinoma of head and neck and a phase I/II study to evaluate safety and eYcacy of P276-00 in combination with gemcitabine in patients with pancreatic cancer.…”
Section: Selective Inhibitorsmentioning
confidence: 99%
“…6) is a highly speciWc inhibitor of CDK2 (IC 50 = 10 nM), which is much less selective toward CDK1 (IC 50 = 110 nM) and CDK4 (IC 50 = 130 nM), with no signiWcant activity toward 12 other kinases tested (IC 50 = 2 M). It showed potent antiproliferative eVects against various human cancer cell lines, such as MCF-7 and H-460 (Joshi et al 2007). Several phase I/II clinical studies with P279-00 have been initiated, such as an open-label, multicenter phase I/II study of selective cyclin-dependent kinase inhibitor P276-00 in combination with radiation in subjects with recurrent and/or locally advanced squamous cell carcinoma of head and neck and a phase I/II study to evaluate safety and eYcacy of P276-00 in combination with gemcitabine in patients with pancreatic cancer.…”
Section: Selective Inhibitorsmentioning
confidence: 99%
“…18,19 The drug was dissolved in dimethyl sulfoxide (DMSO; Sigma Chemical, St Louis, MO, USA) at a concentration of 200 mmol/l (200 mM) and stored at À20 1C until use; it was diluted in culture medium (1-4000 nM, o0.1% DMSO in the final concentration) immediately before use and was used within 4 h.…”
Section: P276-00mentioning
confidence: 99%
“…Independent from good antitumorigenic effects in preclinical studies, in 2008 only low specificity of flavopiridol for Cdk has been demonstrated due to nanomolar affinity to also 25 other protein kinases, like GSK3 and ERK (Karaman et al, 2008), maybe leading to discouraging results in some clinical trials (see next section). Screening of about hundred compounds structurally related to flavopiridol identified P276-00 as potent Cdk specific inhibitor with moderate selectivity for Cdk1, Cdk4, and Cdk9 (Joshi et al, 2007a). Similar to flavopiridol, P276-00 showed antiproliferative and proapoptotic activity in human breast, colon, lung, prostate carcinoma, and promyelocytic leukemia cell lines in vitro (Joshi et al, 2007b).…”
Section: Overview Of Small Molecule Cdk Inhibitors: Selectivity and Mmentioning
confidence: 99%